The politics of electricity supply to Agriculture: Analysis of political actors, discourses, and strategies - Birner, Regina; Sharma, Neeru (International Food Policy Research Institute, 2011)
This chapter presents the information derived from the stakeholder interviews, guided by the conceptual framework presented in Chapter 3. The first section describes the major actors and their interests as well as their political resources and strategies, with the exception of the major political parties, which are discussed in Chapter 9. The second section identifies major discourse coalitions and describes their belief systems and discourses. The third section reflects on the extent to which policy learning across coalitions has taken place or could take place. This information provides the basis for an analysis of the political feasibility of different reform options and strategies, which is presented in Chapter 11.